An Evaluation of English Language Teaching in Indonesian Schools - Mubarok, Husni; Sofiana, Nina (KnE Social Sciences, 2022)
This study discusses the planning, implementation, and assessment processes of English language teaching based on the national curriculum of Indonesia. Evaluative research was conducted using the CIPP model, which stands for context, input, process, and product. The subjects of this study were 30 English teachers from 15 schools in three municipalities in Central Java Province, Indonesia. Data were collected through interviews, questionnaires, and surveys. There are four variables in this research with six sub-variables (school policy, lesson plan, resources and learning facilities, media selection, teaching phases, and assessment). The results of the study show that learning English in both public and private schools has been going well at all levels. The authors recommend that while making a policy on English language teaching in Indonesia, two aspects must be considered – an English learning program based on the applicable curriculum and an extracurricular English learning program. Keywords: English Language Teaching (ELT), national curriculum